Social Media Data Analytics for Marketing Strategies: The Path from Data to Value - Benslama, Teissir; Jallouli, Rim (Journal of Telecommunications and the Digital Economy, 2022)
The analysis of social media data to extract new insights has attracted much attention, especially in the field of Marketing. Few researchers, however, have studied both the concepts of Social Media Data Analytics (SMDA) and Marketing Strategies. Previous publications have only focused on a particular technique or a well-defined Marketing Strategy in a specific context. To address this gap, this paper aims to explore how Social Media Data Analytics can guide and affect Marketing Strategies, and provide an overview of the range of Social Media Data Analytics techniques related to Marketing Strategies. We conducted a systematic review of 120 papers published between 2015 and 2021 on SMDA in Marketing. The findings are presented in terms of the main social media platforms, publication date, journal quality, social media data types, analytical techniques, fields of application, firm size, and related Marketing Strategies. The SMDA techniques are classified into six categories: Sentiment Analysis, Artificial Intelligence, Data Mining, Statistics, Coding and Modelling, and Simulation. A set of detailed Marketing Strategies guided by SMDA are also presented, as well as an integrative framework mapping how SMDA creates value. The results highlight several SMDA techniques that still lack exploration and outline their relevance.